Applications of Graphene and Its Derivatives in Bone Repair: Advantages for Promoting Bone Formation and Providing Real-Time Detection, Challenges and Future Prospects - Du Z (Dove Medical Press, 2020)
Zhipo Du1 *,* Cunyang Wang2 *,* Ruihong Zhang,3 Xiumei Wang,4 Xiaoming Li2 1Department of Orthopedics, The Fourth Central Hospital of Baoding City, Baoding 072350, Hebei Province, People’s Republic of China; 2Key Laboratory for Biomechanics and Mechanobiology of Ministry of Education, School of Biological Science and Medical Engineering, Beijing Advanced Innovation Center for Biomedical Engineering, Beihang University, Beijing 100083, People’s Republic of China; 3Department of Research and Teaching, The Fourth Central Hospital of Baoding City, Baoding 072350, Hebei Province, People’s Republic of China; 4Key Laboratory of Advanced Materials of Ministry of Education, Tsinghua University, Beijing 100084, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruihong Zhang; Xiaoming Li Tel +86-312-6413166Tel +86-10-82316467Email 13931391449@163.com x.m.li@hotmail.comAbstract: During continuous innovation in the preparation, characterization and application of various bone repair materials for several decades, nanomaterials have exhibited many unique advantages. As a kind of representative two-dimensional nanomaterials, graphene and its derivatives (GDs) such as graphene oxide and reduced graphene oxide have shown promising potential for the application in bone repair based on their excellent mechanical properties, electrical conductivity, large specific surface area (SSA) and atomic structure stability. Herein, we reviewed the updated application of them in bone repair in order to present, as comprehensively, as possible, their specific advantages, challenges and current solutions. Firstly, how their advantages have been utilized in bone repair materials with improved bone formation ability was discussed. Especially, the effects of further functionalization or modification were emphasized. Then, the signaling pathways involved in GDs-induced osteogenic differentiation of stem cells and immunomodulatory mechanism of GDs-induced bone regeneration were discussed. On the other hand, their applications as contrast agents in the field of bone repair were summarized. In addition, we also reviewed the progress and related principles of the effects of GDs parameters on cytotoxicity and residues. At last, the future research was prospected.Keywords: graphene, graphene oxide, bone repair, real-time detection, signaling pathways